THE UNINTENTIONAL VIOLENCE IN THE JOKES ABOUT THE INDIGENOUS MANGYANS OF ORIENTAL MINDORO, PHILIPPINES - Jerwin M. Mahaguay (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This paper examines the intention within the violence inherent in the jokes directed towards the indigenous (IPs) Mangyans of Oriental Mindoro, Philippines. It has two parts. The first part focuses on exposing how these jokes originated and transferred. The second part deals with tracing the intentions behind uttering these jokes.